2020
DOI: 10.1158/1078-0432.ccr-19-2853
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Is Associated with Lower Risk of PTEN-Null and Lethal Prostate Cancer

Abstract: Purpose: Statins are associated with lower risk of aggressive prostate cancer, but lethal prostate cancer is understudied and contributing mechanisms are unclear. We prospectively examined statins and lethal prostate cancer risk in the Health Professionals Follow-up Study (HPFS), tested associations with molecular subtypes, and integrated gene expression profiling to identify putative mechanisms. Experimental Design: Our stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In the present study, we attempted to use the FDA-approved drugs Simvastatin and Verteporfin to achieve pharmacological inhibition of key nodes in the MYBL2/RACGAP1/RhoA/YAP signaling cascade and found that these treatment regimens were sufficient to reverse ADT resistance and the metastatic phenotype in CRPC cells. Consistent with our results, growing evidence supports the role of statins in reducing the risk of advanced and lethal PCa 60 . Further clinical trials have shown that statins are promising candidates for adjuvant therapy with abiraterone in patients with metastatic CRPC and correlated with superior overall survival 61 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we attempted to use the FDA-approved drugs Simvastatin and Verteporfin to achieve pharmacological inhibition of key nodes in the MYBL2/RACGAP1/RhoA/YAP signaling cascade and found that these treatment regimens were sufficient to reverse ADT resistance and the metastatic phenotype in CRPC cells. Consistent with our results, growing evidence supports the role of statins in reducing the risk of advanced and lethal PCa 60 . Further clinical trials have shown that statins are promising candidates for adjuvant therapy with abiraterone in patients with metastatic CRPC and correlated with superior overall survival 61 .…”
Section: Discussionsupporting
confidence: 92%
“…Another analysis of 1,001 prostate cancer patients (289 statin users) reported a 0.19 hazard ratio for prostate cancer-specific death among statin users compared with men who did not use statins (95% CI, 0.06–0.56) [ 66 ]. A recent clinical study showed that statin use is associated with a reduced risk of phosphatase and tensin homolog (PTEN)-negative and fatal prostate cancer [ 23 ]. However, the results of a population-based epidemiologic study showed that the use of statins was not associated with overall prostate cancer risk [ 67 ], although the credibility of the results of the study are open to question due to the relatively small sample size and the existence of potential selection and recall biases.…”
Section: Anti-tumor Effects Of Statinsmentioning
confidence: 99%
“…The Pten-null senescent PCa tumors from mice had high infiltration of MDSCs in the TME promoted by activation of the Janus kinase (JAK)2/STAT3 pathway and secretion of chemoattractant molecules to the TME [57,58]. A recent populationbased study of >6000 PCa related PTEN loss to the statin pathway and inflammation and immune activation in lethal PCa [66]. These findings are supported by a new study of Pten knockout mice, which used methylation and transcriptomic profiling to show that loss of PTEN drives global changes in DNA CpG methylation with associated gene expression changes, thus affecting several inflammatory and immune molecular pathways during PCa development [65].…”
Section: Phosphatase and Tensin Homologue (Pten)mentioning
confidence: 99%